Выкуп: роман / Д. Стил ; пер. с англ. В. Н. Матюшиной - Стил Даниэла (АСТ, 2007)
Экземпляры: абонемент (20200611) / Инвентарный номер: 28080 / Цена: / Сис.шифр: 84(7Сое) / Авт.знак: С 80 / ББК: 84(7Сое)